The Impact of Incentive Alignment in Behavioral Acceptance - Aziz, Saliza Abdul; Idris, Kamil Md (International Journal of Economics and Financial Issues, 2016)
The purpose of this paper is to highlight on the behavioral intention in technology application. The form of tax e-filing technology introduced in Malaysia particularly on corporate taxation is, however, not fully utilized, despite the enormous amount of budget allocated for this matter. As such, the present research is attempted to discover enrichment the model of acceptability in a situation where authority is involved in encouraging professionals (tax agents/preparers) to adopt the proposed system. Thus, the integration of The Operant Conditioning Theory (OCT) is expected to give a new outlook to the existing model. It is supposed to reveal the non-compliance behavior towards corporate tax e-filing acceptability among tax agents/preparers in Malaysia. Even though this Unified Theory of Acceptance and Use of Technology (UTAUT) model is accepted and integrated into many studies of various fields, their results revealed some inconsistencies when applied in different areas or situations. This paper is the first attempt in tax e-filing application which considered the element of incentive in behavioral intention. The empirical research findings would be of significance to record and enhance the UTAUT knowledge indirectly. Keywords: Incentive alignment, Partial Least Square, The Operant Conditioning Theory JEL Classification: